Piłka nożna, styl życia i procesy reprodukcji kulturowej w Stanach Zjednoczonych - Melosik, Zbyszko (Studia Edukacyjne, 2020)
In his article the author considers the paradox of soccer appropriation in the United States. It is rejected by majority of Americans at the professional level as they prefer football, basketball and baseball. However, at the recreational level soccer is used by middle class and upper middle class as a form of their status confirmation and for cultural reproduction. The symbol of such an approach is analysed – the „soccer mom” as a person who considers soccer as a very valuable exercise experience for her daughters and sons.